Morphology and multi-locus phylogeny reveal a new coffee-associated saprobic Rhamphoriopsis (Rhamphoriaceae, Rhamphoriales) species in Yunnan Province, China - Pitakpattanakul, Chutimaphon; Han, Mei-Yan; Karunarathana, Samantha C.; Lu, Wen-Hua; Zheng, De-Ge; Chia, Poosanisa; Bunphan, Jedsada; Dai, Dong-Qing; Elgorban, Abdallah M.; Chukeatirote, Ekachai; Tibpromma, Saowaluck (Phytotaxa, 2025)
During investigations of saprobic fungi associated with Coffea arabica in Puʹer City, Yunnan Province, China, a Rhamphoriopsis species was collected and isolated from decaying coffee branches and is introduced herein as R. uniseptata sp. nov. The new species was identified based on morphological characteristics and phylogenetic analyses (Maximum Likelihood and Bayesian Inference analyses) of combined ITS, LSU, SSU, tef1-α, and rpb2 sequence data. Distinct morphological characteristics, together with a multi-locus phylogeny, support the placement of R. uniseptata as a new taxon within the genus. This study expands current knowledge of Rhamphoriopsis diversity and highlights the ecological significance of saprobic fungi in coffee cultivation systems. This finding provides a foundation for further research into the taxonomy.